The formation and development of Latin medical vocabulary - Langslow, D; Langslow, David (1991)
﻿ This is a study of the substantival medical terminology of Aulus Cornelius Celsus (early 1st c.) and Cassius Felix (mid 5th c.), in the fields of Anatomy and Physiology; Pathology; and Therapeutics. Two broad questions are considered: (1) What were the possible and the preferred means of extending the Latin vocabulary in these technical areas in the first and the fifth century A.D.? (2) May any linguistic features be identified as proper or peculiar to Latin medical - or, more generally, technical - terminology? Chapter 1 presents a general characterisation, based on examples of medical language, of modern technical terminology. Certain features of the structure and composition of the modern terminology are observed also in our Latin authors, especially in Cassius Felix. Chapters 2-5 focus each on one linguistic means of term-formation in Celsus and Cassius Felix. These are (Ch.2:) the use of Greek medical terms within the Latin terminology; (Ch.3:) the use of semantic extension, that is the deployment of established Latin words with new, medical reference (sutura 'stitching' → 'cranial suture'); (Ch.4:) the minimal use of compounding (dentifricium 'tooth-rub'), and the use as single terminological units of lexicalised Noun Phrases, Noun + Adjective (ignis sacer a type of skin-disease) or Noun + Genitive (difficultas urinae 'dysury'), here called "Phrasal Terms"; (Ch.5:) the favouring of certain suffixes in deriving Nouns (and some Adjectives) and the striking correlation between suffix and the lexical-semantic field of the derivative (-or and clinical signs and symptoms: dolor, rubor). Chapter 6 presents comparative figures for the two authors and a general working hypothesis that emerges: namely that divergences between Cassius Felix and Celsus may be interpreted as symptoms of the development of a Latin technical medical terminology (notably the integration of Greek and Latin terminology; reduction in the use of non-metaphorical polysemy; increased use of Phrasal Terms in fixed word order; extended use of suffixation to signal the semantic organisation of the terminology and, additionally, to form nominalisations as part of the development of a heavily-nominal style). A programme is adumbrated for testing this hypothesis. Volume II contains brief historical introductions to Celsus and Cassius Felix, the authors and their works; a Glossary of their medical terminology in three parts (ANATOMY and PHYSIOLOGY; PATHOLOGY; THERAPEUTICS); and full word indexes to both authors listed on microfiche.